Changes in Muscle Activity Patterns and Joint Kinematics During Gait in Hemophilic Arthropathy - Cruz-Montecinos, Carlos; Pérez-Alenda, Sofía; Querol, Felipe; Cerda, Mauricio; Maas, Huub (Frontiers in Physiology, 2020)
Haemophilic arthropathy is the result of repetitive intraarticular bleeding and synovial inflammation. In people with haemophilic arthropathy (PWHA), very little is known about the neural control of individual muscles during movement. The aim of the present study was to assess if the neural control of individual muscles, coordination between antagonistic muscle pairs and joint kinematics during gait are affected in PWHA. Thirteen control subjects (CG) walked overground at their preferred and slow velocity (1 m/s) and fourteen PWHA walked overground at the preferred velocity (1 m/s). Joint kinematics and temporal gait parameters were assessed using four inertial sensors. Surface electromyography (EMG) was collected from Gluteus Maximus (GMAX), Gluteus Medius (GMED), Vastus Medialis (VM), Vastus Lateralis (VL), Rectus Femoris (RF), Medial Gastrocnemius (MG), Lateral Gastrocnemius (LG), Soleus (SOL), Tibialis Anterior (TA), Rectus Femoris (RF), Semitendinosus (ST), and Biceps Femoris (BF). Waveforms were compared using the time-series analysis through Statistical Parametric Mapping. In PWHA compared to CG, EMG amplitude during the stance phase was higher for LG (for both velocities of the CG), BF (slow velocity only) and ST (preferred velocity only) (p<0.05). Co-contraction during the stance phase was higher for MG-TA, LG-TA, VL-BF, VM-ST, LG-VL and MG-VM (both velocities) (p<0.05). MG and LG were excited earlier (preferred velocity only) (p<0.05). A later off-set during the stance phase was found for VL, BF and ST (both velocities) and BF and GMAX (preferred velocity only) (p<0.05). In addition, the range of motion in knee and ankle joints was lower in PWHA (both velocities) and hip joint (preferred velocity only) (p<0.05). In conclusion, the neural control of individual muscles and coordination between antagonistic muscles during gait in PWHA differs substantially from controls subjects.